Benzylic C−H Functionalisation by [Et3SiH+KOtBu] leads to Radical Rearrangements in o‐tolyl Aryl Ethers, Amines and Sulfides. Issue 11 (24th April 2020) - Arokianathar, Jude N.; Kolodziejczak, Krystian; Bugden, Frances E.; Clark, Kenneth F.; Tuttle, Tell; Murphy, John A.
Abstract: Reaction of Et3 SiH+KO t Bu with diaryl ethers, sulfides and amines that feature an ortho alkyl group leads to rearrangement products. The rearrangements arise from formation of benzyl radicals, likely formed through hydrogen atom abstraction by triethylsilyl radicals. The rearrangements involve cyclisation of the benzyl radical onto the partner arene, which, from computation, is the rate determining step. In the case of diaryl ethers, Truce‐Smiles rearrangements arise from radical cyclisations to form 5‐membered rings, but for diarylamines, cyclisations to form dihydroacridines are observed. Abstract :